Metronomic chemotherapy in patients with advanced neuroendocrine tumors: A single‐center retrospective analysis. (16th August 2022) - Arrivi, Giulia; Spada, Francesca; Frassoni, Samuele; Bagnardi, Vincenzo; Laffi, Alice; Rubino, Manila; Gervaso, Lorenzo; Fazio, Nicola
Abstract: Neuroendocrine tumors (NETs) are more commonly slow‐growing, therefore patients often receive chronic systemic therapies for tumor growth control and preservation of quality of life. Metronomic chemotherapy (mCT) is in line with this goal as it leads to stabilization of tumor growth over time without severe systemic toxicity. This is a retrospective analysis of patients with metastatic NETs receiving metronomic capecitabine (mCAP) or temozolomide (mTEM), at a NET‐referral center. The aims of the study were to explore activity and safety of mCT and relationships between some characteristics of the patient population and clinical outcomes. Among a total of 67 patients with metastatic well or moderately differentiated (W/M‐D) NETs, mostly gastroenteropancreatic (GEP) and nonfunctioning, 1.2 years (95% CI: 0.8–1.8) median progression‐free survival (mPFS), and 3.0 years (95% CI: 2.3–4.9) median overall survival (mOS) were observed. Disease control rate was 85%. Grade 3 adverse events occurred in 15% of patients in mCAP and 13% in mTEM, and were mostly hematological and gastrointestinal. At univariate and multivariate analysis none of the variables analyzed (treatment regimen, sex, age at diagnosis, site of primary tumor and metastases, number of previous mCT lines, baseline tumor status before mCT, Ki67 value) were significantly correlated to OS and PFS. Our retrospective study suggested that mCAP and mTEM can be active and well tolerated in patients with metastatic W/M‐D NETs, irrespective of the primary site, site of metastases, line of treatment and baseline tumor status. Abstract : Our retrospective analysis showed that metronomic chemotherapy can be active and well tolerated in patients with metastatic well to moderate differentiated NETs, irrespective of the primary site, site of metastases, line of treatment and baseline tumor status.